Molecular defects in cardiovascular disease - Dhalla, Naranjan S.; Nagano, Makoto 1928-; Oésítâadal, Bohuslav (Springer, 2011)
Molecular Defects in Cardiovascular Disease provides an in-depth discussion of the molecular mechanisms underlying the genesis of cardiovascular defects and the implications this has on current and emerging targeted therapeutics.  Divided into three sections, this book covers the scientific foundations of our present understanding as well as the array of clinical manifestations and their treatment.  The first section covers Molecular Mechanisms of Heart Disease, with discussion of the development of cardiovascular dysfunction.  The remaining two sections provide a more clinical focus.  The second, Cardiac Hypertrophy and Heart Failure deals with metabolic derangements, Ca2+ handling, and subcellular remodeling.  It illustrates the wide variety of molecular defects which may serve as targets associated with the transition from cardiac hypertrophy to advanced heart failure.  The third section, Hypertension and Diabetes, provides molecular rationale for the pathogenesis of hypertension and diabetic cardiomyopathy, as well as highlighting the importance of hormones toward this end.    A necessary resource for clinicians and researchers, this book elucidates the experimental basis of the practice of cardiology.  It is the culmination of our advances in the understanding of cardiovascular molecular biology and a blueprint for the efficacious use of targeted therapies.